PD-1 inhibitors plus oxaliplatin or cisplatin-based chemotherapy in first-line treatments for advanced gastric cancer: A network meta-analysis - Guo, Xiaoyu; Yang, Bowen; He, Lingzi; Sun, Yiting; Song, Yujia; Qu, Xiujuan (Frontiers in Immunology, 2022)
Background: Currently, there has been no direct comparison between programmed cell death protein 1 (PD-1) inhibitors plus different chemotherapy regimens in first-line treatments for advanced gastric cancer (AGC). This study performed a network meta-analysis (NMA) to evaluate the efficacy and safety of PD-1 inhibitors plus oxaliplatin- or cisplatin-based chemotherapy. Methods: PubMed, Embase, and the Cochrane Central Register were used to seek a series of phase III randomized controlled trials (RCTs) studying on first-line PD-1 inhibitors plus chemotherapy and phase III RCTs comparing first-line oxaliplatin and cisplatin-based chemotherapy for AGC to perform NMA. The main outcome was overall survival (OS) and other outcomes included progression-free survival (PFS), objective response rate (ORR), and treatment-related adverse events (TRAEs). Results: Eight eligible RCTs involving 5723 patients were included. Compared with PD-1 inhibitors plus cisplatin-based chemotherapy, PD-1 inhibitors plus oxaliplatin-based chemotherapy could prolong the OS without statistical significance (hazard ratio [HR]: 0.82, 95% credible interval [CI]: 0.63-1.06). However, for patients with combined positive score (CPS) ≥ 1, PD-1 inhibitors plus oxaliplatin-based chemotherapy significantly prolonged the OS (HR: 0.75, 95% CI: 0.57-0.99). PFS in PD-1 inhibitors plus oxaliplatin-based chemotherapy was significantly longer than that in PD-1 inhibitors plus cisplatin-based chemotherapy (HR 0.72, 95% CI: 0.53-0.99). Regarding safety, the incidence of ≥ 3 TRAEs was similar between PD-1 inhibitors plus oxaliplatin-based chemotherapy and PD-1 inhibitors plus cisplatin-based chemotherapy (RR: 0.86, 95% CI: 0.66-1.12). The surface under the cumulative ranking area curve (SUCRA) indicated that PD-1 inhibitors plus oxaliplatin-based chemotherapy ranked first for OS (97.7%), PFS (99.3%), and ORR (89.0%). For oxaliplatin-based regimens, there was no significant difference between nivolumab plus oxaliplatin-based chemotherapy and sintilimab plus oxaliplatin-based chemotherapy in terms of OS, PFS, ORR, and ≥3 TRAEs. Conclusion: Compared with PD-1 inhibitors plus cisplatin-based chemotherapy, PD-1 inhibitors plus oxaliplatin-based chemotherapy significantly prolonged PFS. Considering both efficacy and safety, PD-1 inhibitors plus oxaliplatin-based chemotherapy might be a better option in the first-line treatment for AGC.